Sistem Informasi Bimbingan Online Menggunakan Fitur Logbook Konsultasi - Muhajirin, Muhajirin; Rika, Rika; Arafah, Muhammad; M. Sabir, Fitriana; Pasnur, Pasnur; Maslihatin, Tatik; Ilham, Ilham; Resha, Muhammad (STMIK KHARISMA Makassar, 2024)
The Final Project guidance process often faces obstacles such as inflexible schedules, limited space and time, and difficulties in communication between supervisors and students directly. This study aims to implement a web-based Final Project guidance system using the Laravel framework designed using the Waterfall method and the PHP programming language and MySQL as a database. Data in this study were obtained through observation, literature studies and interviews. Testing in this study was carried out using the Black Box method and User Acceptance Testing (UAT). The results showed that this application was feasible for use by students and lecturers with an average test score on the Usability aspect of 86.68%, on the Information Quality aspect of 84.88%, and on the Service Interaction Quality aspect of 83.86%. Based on the feasibility category interval of 81% - 100%, this system was declared very feasible for use, in addition this system was able to overcome traditional obstacles in the Final Project guidance process.